DEFLATIONISM AND PHILOSOPHY - Garcia Zarate, Oscar Augusto (2006)
The philosophical stages depending on the linguistic and post-linguistictum are a general background for the birth of deflationism as it is knownnowadays. This article states that in order to understand linguistic turn'smethodological features we have to understand how this movement isrelated to previous trends in the history ofWestem philosophy. This done,we will have a proper understanding of deflationism's core idea and itsinternal development.